1983
DOI: 10.1111/j.1751-1097.1983.tb03857.x
|View full text |Cite
|
Sign up to set email alerts
|

ELECTRON SPIN RESONANCE OF MELANIN FROM HAIR. EFFECTS OF TEMPERATURE, pH AND LIGHT IRRADIATION

Abstract: Abstract— The variation with temperature, pH and light of the ESR signal of hydrated melanin powders from Japanese black hair has been studied. An explanation of the results is proposed on the basis of quinhydrone type complexes and of acid‐base equilibria of melanin and its semiquinone radicals. During exposure to light of wavelengths 254–600 nm, both stable and unstable radicals have been observed. The action spectrum for the formation of stable melanin radicals has been determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The decrease in intrinsic free radical concentration in hydrated hair and then an increase upon exposure to light seem t o reflect the involvement of water in the melanin complex. Our results agree with the model proposed by Arnaud et al (1983), who explained the participation of water in melanin free radicals in solid melanins, as well as in KBr dispersion. Water molecules preferentially solvate hydrogen-bonded acceptor or donor sites, which will decrease in concentration of radicals in the presence of water.…”
Section: Resultssupporting
confidence: 92%
“…The decrease in intrinsic free radical concentration in hydrated hair and then an increase upon exposure to light seem t o reflect the involvement of water in the melanin complex. Our results agree with the model proposed by Arnaud et al (1983), who explained the participation of water in melanin free radicals in solid melanins, as well as in KBr dispersion. Water molecules preferentially solvate hydrogen-bonded acceptor or donor sites, which will decrease in concentration of radicals in the presence of water.…”
Section: Resultssupporting
confidence: 92%
“…This could explain why somewhat narrower 13 C resonances were obtained in the case of Human hair melanin in comparison with the Sepia melanin. Literature ESR data on melanin obtained from Japanese black hair 21 also shows a single absorption line; however, the free radical concentration differed and was found to be 3.6 ð 10 18 free radicals g 1 . The difference in free radical content can be attributed to several factors, such as water content (known to reduce the ESR signal) and pH (increased acidity reduces the signal, whereas increased basicity increases the ESR signal).…”
Section: Human Hair Melaninmentioning
confidence: 84%
“…It is confirmed that melanin plays the most important protective role against UV radiation in the skin …”
Section: Introductionmentioning
confidence: 83%